The Arabidopsis DUF239 gene family encodes Neprosin‐like proteins that are widely expressed in seed endosperm. Issue 1 (2nd December 2022) - Vergès, Valentin; Bellenger, Léo; Pichon, Olivier; Giglioli‐Guivarc'h, Nathalie; Dutilleul, Christelle; Ducos, Eric
Abstract: Domain of unknown function 239 (DUF239) is a conserved sequence found in the catalytic site of Neprosins which are specific secreted prolyl endopeptidases found in the Nepenthes genus. Neprosins participate in the nitrogen cycle by digesting preys trapped in the pitcher of these carnivorous plants. Apart from that, DUF239s have been poorly documented in plants. We have identified 50 genes containing DUF239‐coding sequences in the Arabidopsis genome that are distributed across six distinct phylogenetic clusters. The chromosomal distribution suggests that several genes are the result of recent duplication events, with up to eight genes found in a strict tandem distribution. In Arabidopsis, most of DUF239‐containing sequences are also associated to a Neprosin‐activating domain (DUF4409) and an amino‐terminal α‐helix which corresponds to the typical domain organization of the Neprosins described in the Nepenthes genus. Analysis of Arabidopsis transcriptomic datasets reveals that 39 genes are exclusively expressed in reproductive organs, mainly during seed development and more specifically in the endosperm (23 genes). The peculiar expression pattern of the DUF239 gene family in Arabidopsis suggests new functions of Neprosin‐like proteins in plants during seed development. Core Ideas: The DUF239 gene family of Arabidopsis consists of 50 members. Arabidopsis DUF239 proteins share a similar domain organization with Neprosin‐like peptidases. The DUF239 genes arise from ancient and recent gene duplication events. The DUF239 genes are widely expressed in seed endosperm.